Hierarchically Structured Composite Fibers for Real Nanoscale Manipulation of Carbon Nanotubes. (29th January 2021) - Xu, Weiheng; Ravichandran, Dharneedar; Jambhulkar, Sayli; Zhu, Yuxiang; Song, Kenan
Abstract: Carbon nanotube (CNT)‐reinforced polymer fibers have broad applications in electrical, thermal, optical, and smart applications. The key for mechanically robust fibers is the precise microstructural control of these CNTs, including their location, dispersion, and orientation. A new methodology is presented here that combines dry‐jet‐wet spinning and forced assembly for scalable fabrication of fiber composites, consisting of alternating layers of polyacrylonitrile (PAN) and CNT/PAN. The thickness of each layer is controlled during the multiplication process, with resolutions down to the nanometer scale. The introduction of alternating layers facilitates the quality of CNT dispersion due to nanoscale confinement, and at the same time, enhances their orientation due to shear stress generated at each layer interface. In a demonstration example, with 0.5 wt% CNTs loading and the inclusion of 170 nm thick layers, a composite fiber shows a significant mechanical enhancement, namely, a 46.4% increase in modulus and a 39.5% increase in strength compared to a pure PAN fiber. Beyond mechanical reinforcement, the presented fabrication method is expected to have enormous potential for scalable fabrication of polymer nanocomposites with complex structural features for versatile applications. Abstract : The innovative fabrication method presented combines traditional dry‐jet‐wet fiber spinning and forced assembly for hierarchical nano‐microstructures consisting of polyacrylonitrile and carbon nanotubes (CNTs). With increasing layer numbers and decreasing layer thickness, down to 170 nm, the composite fiber shows improved mechanical properties due to selective deposition, continuous lining, and preferential alignment of CNTs.